2013
DOI: 10.3724/sp.j.1141.2012.04421
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of weight-cutting effect in Pu-erh tea

Abstract: Abstract:Originally grown and produced in southern of Yunnan, China, Pu-erh tea has a long history and carries rich cultural connotations. Consumption of Pu-erh has been thought to possess numerous health benefits including weight-loss, lowering of blood glucose levels, and preventing cardiovascular diseases. Research on humans, rodents, and cell lines have each confirmed that Pu-erh tea indeed displays weight-loss and blood lipid lowering effects. The main bioactive components, such as theabrownin (TB), polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…At the beginning of the treatment, PTE treatment did not show an effect on lowering body weight. However, PTE reduced OVX-induced body weight gain in rats only after 6 weeks of treatment, suggesting that long-term tea drinking has a positive effect on weight loss, which is consistent with the results of previous studies (Zou et al, 2012). Notably, osteoporosis results from an imbalance related to faster bone resorption than bone formation.…”
Section: Discussionsupporting
confidence: 92%
“…At the beginning of the treatment, PTE treatment did not show an effect on lowering body weight. However, PTE reduced OVX-induced body weight gain in rats only after 6 weeks of treatment, suggesting that long-term tea drinking has a positive effect on weight loss, which is consistent with the results of previous studies (Zou et al, 2012). Notably, osteoporosis results from an imbalance related to faster bone resorption than bone formation.…”
Section: Discussionsupporting
confidence: 92%
“…Zou et al . () reported that polysaccharides, polyphenols, theabrownin and statins in Puerh tea may downregulate the biosynthesis of fat to reduce body weight and upregulate the oxidation of fat and reduce lipid profiles. In addition, gallic acid was also shown to have an effect on attenuating visceral fat accumulation, cholesterol parameters and weight reduction in an animal model (Kubota et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…These include polyphenols, theabrownin, statins, tea polysaccharides, tea catechins, caffeine, gallic acid, protein, amino acids, alkaloids, vitamins, carbohydrates, minerals and γ-aminobutyric acid (Duh et al, 2004). Zou et al (2012) reported that polysaccharides, polyphenols, theabrownin and statins in Puerh tea may downregulate the biosynthesis of fat to reduce body weight and upregulate the oxidation of fat and reduce lipid profiles. In addition, gallic acid was also shown to have an effect on attenuating visceral fat accumulation, cholesterol parameters and weight reduction in an animal model (Kubota et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al. reported that tea polysaccharides and theabrownin may downregulate the biosynthesis of fat to reduce body weight and upregulate the oxidation of fat and reduce lipid profiles. Gallic acid was shown to decrease the body weight and the weights of the liver and adipose tissue in rat models of diet‐induced obesity .…”
Section: Discussionmentioning
confidence: 99%